KAJIAN PEMANFAATAN TEPUNG SUKUN DAN TEPUNG AMPAS KELAPA DALAM PEMBUATAN FLAKES - ANIS KOMALA; YUSMARINI YUSMARINI; RAHMAYUNI RAHMAYUNI (Jurnal Sagu, 2017)
The purpose of this research was to obtain the best formulation between the breadfruit flour and flourcoconut pulp for making flakes. The research used a completely Randomized Design (CRD) with five treatmentsand three replications. The treatments of this research were ratio between breadfruit flour and flour coconutpulp (80:0,75:5,70:10,65:15,60:20) with the addition of tapioca at 20%. Data were statistically analyzedusing Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) test at5% level. The best formula was a formula with ratio of breadfruit flour and flour coconut pulp of 65:15.Chemical analysis such as moisture content 6.39%, ash content 2.36%, fat content 7.51%, protein content5.12%, carbohydrate content 78.63%, crude fiber content 3.62%, and durability crunchy in milk was 5.50minute. The result of the descriptive test of the flakes from the best treatment was a light brown, slightlyscented breadfruit, hard texture without and with added of milk, and coconut taste, while hedonic test oncolor, aroma, texture without and with addition of milk, taste, and overall were liked by panelists.